Creativity & human development - Creativity Centre Educational Trust (The Creativity Centre Educational Trust, 2012)
Covering a wide range of topics relating to creativity and human development with an emphasis on a cross-cultural exchange of research and ideas.
Keywords: Creative ability : Periodicals; Developmental psychology : Periodicals; Créativité : Périodiques; Psychologie du développement : Périodiques; Developmental psychology; Creative ability